Snow patches in nival landscapes and their role for the Ice Complex formation in the Laptev Sea coastal lowlands. - Kunitsky, Victor V; Schirrmeister, Lutz; Grosse, Guido; Kienast, Frank (PANGAEA, 2002)
In wide areas of Northern Siberia, glaciers have been absent since the Late Pleistocene. Therefore, ground ice and especially ice wedges are used as archives for paleoclimatic studies. In the present study, carried out on the Bykovsky Peninsula, eastern Lena Delta, we were able to distinguish ice wedges of different genetic units by means of oxygen and hydrogen isotopes. The results obtained by this study on the Ice Complex, a peculiar periglacial phenomenon, allowed the reconstruction of the climate history with a subdivision of a period of very cold winters (60-55 ka), followed by a long stable period of cold winter temperatures (50-24 ka), Between 20 ka and 11 ka, climate warming is indicated in stable isotope compositions, most probably after the Late Glacial Maximum. At that time, a change of the marine source of the precipitation from a more humid source to the present North AtIantic source region was assumed. For the Ice Complex, a continuous age-height relationship was established, indicating syngenetic vertical ice wedge growth and sediment accumulation rates of 0.7 m/ky. During the Holocene optimum, ice wedge growth was probably limited due to the extensive formation of lacustrine environments. Holocene ice wedges in thermokarst depressions (alases) and thermoerosional valleys (logs) were formed after climate deterioration from about 4.5 ka until the present. Winter temperatures were warmer at this time as compared to the cooler Pleistocene. Migration of bound water between ice wedges and segregated ice may have altered the isotopic composition of old ice wedges. The presence of ice wedges as diagnostic features for permafrost conditions since 60 ka, implies that a large glacier extending over the Laptev Sea shelf did not exist. For the remote non-glaciated areas of Northern Siberia, ice wedges were established as a powerful climate archive.
Tab. 1+7: Hydrochemical analyses of firn and meltwater from different "cold" snow patches
Keywords: Area/locality; Bicarbonate ion; Calcium; Chloride; Clastic material; cold-1; cold-2; cold-3; cold-4; cold-5; cold-6; Date/Time of event; Length; Location of event; Magnesium; Nivation hollow on kar slope; Chekanovsky Ridge; Nivation hollow on kar slope Kunga Ridge; Nivation hollow on upper rim of cryoplanation terrace; Chekanovsky Ridge; Nivation hollow on upper rim of cryoplanation terrace Chekanovsky Ridge; Oxidation reduction (RedOx) potential; pH; Ravine; Bykovsky Peninsula; Sample code/label; Sodium; Sulfate; Thickness; Width